2018
DOI: 10.20945/2359-3997000000031
|View full text |Cite
|
Sign up to set email alerts
|

Androgen insensitivity syndrome: a review

Abstract: Androgenic insensitivity syndrome is the most common cause of disorders of sexual differentiation in 46,XY individuals. It results from alterations in the androgen receptor gene, leading to a frame of hormonal resistance, which may present clinically under 3 phenotypes: complete (CAIS), partial (PAIS) or mild (MAIS). The androgen receptor gene has 8 exons and 3 domains, and allelic variants in this gene occur in all domains and exons, regardless of phenotype, providing a poor genotype - phenotype correlation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
93
0
9

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 118 publications
(148 citation statements)
references
References 63 publications
1
93
0
9
Order By: Relevance
“…There may also be a slight loss of function of AR contributing to SBMA pathogenesis (Thomas et al, 2006). However, motor impairment has not been observed in AR knockout mice (Yeh et al, 2002) or in severe testicular feminisation patients lacking AR function (Batista et al, 2018). Interestingly, recent reports have shown that muscle may play a more prominent part in disease than previously thought and indeed may be a key site of AR toxicity and the development of pathology in SBMA (Cortes et al, 2014a;Lieberman et al, 2014;Milioto et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…There may also be a slight loss of function of AR contributing to SBMA pathogenesis (Thomas et al, 2006). However, motor impairment has not been observed in AR knockout mice (Yeh et al, 2002) or in severe testicular feminisation patients lacking AR function (Batista et al, 2018). Interestingly, recent reports have shown that muscle may play a more prominent part in disease than previously thought and indeed may be a key site of AR toxicity and the development of pathology in SBMA (Cortes et al, 2014a;Lieberman et al, 2014;Milioto et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Several different mutations of the AR gene have been identified so far. Some of them might lower its function leading to the androgen insensitivity syndrome [33]; they encompass pathologic conditions which occur with different clinical phenotypes: spinal and bulbar muscular atrophy and partial or complete androgen resistance (i.e., Morris syndrome). Conversely, some other mutations of AR can be activating as it does in prostate cancer.…”
Section: Androgen Receptor: Structure and Functionmentioning
confidence: 99%
“…Complete Androgen Insensitivity in Girls with Inguinal Hernias: A Serendipity Opportunity for Early Diagnosis Rafael Loch Batista 1,2 1 Hospital das Cl ınicas da Universidade de São Paulo, Endocrinology Unit, Laborat orio de Investigações M edicas LIM/42, HCFMUSP, São Paulo/SP, Brazil; 2 Instituto de Psiquiatria HCFMUSP, São Paulo/SP, Brazil…”
Section: Commentarymentioning
confidence: 99%
“…Collectively, these conditions are named 46,XY differences of sexual development (DSD). Androgen insensitivity syndrome (AIS) is the most common cause of DSD in individuals with 46,XY karyotype [2]. At molecular level, it is caused by allelic variants in the AR gene, which is located at X chromosome, conferring a X-linked pattern of inheritance.…”
Section: Commentarymentioning
confidence: 99%